Immigration Supervision Of Refugees And Mandiri Suaka Searchers In The Eks Komando Building, Military District, West Jakarta - Mas Budi Priyatno; Surya Pranata (Jurnal Ilmiah Kajian Keimigrasian, 2020)
The problem of asylum seekers and refugees in Indonesia has become a national problem that needs to be addressed seriously by relevant institutions such as: Immigration Law Human Rights Ministry, Ministry of Foreign Affairs, The Coordinating Ministry for Political, Legal, and Security Affairs of the Republic of Indonesia, Ministry of Home Affairs, local government, TNI, Polri as well as various International and National Organizations, religious leaders, community leaders and so on . Apart from being able to cause a situation that is not conducive to society so that it can create its own unrest, this situation can also threaten the country's sovereignty and security. Supervision and law enforcement have begun to be drafted in clear regulations as well as solid governance and institutional management so that there is clarity regarding the supervision and presence of refugees from entering Indonesia to become refugees, resettlement and final reject in real action.